E-government in Africa: Challenges and Prospects - (:unkn) unknown (My University, 2024)
Developing comprehensive digitalization policies is a formidable challenge for many developing countries, particularly in Africa, where the modernization of the state faces various obstacles. Success in e-government initiatives requires tailored approaches that acknowledge contextual differences. E-government projects in African countries often face funding challenges, relying on donor aid, leading to discontinuation without dedicated funding, hindering incremental improvements. E-government and Open government are seen as strategic solutions to help African countries achieve Sustainable Development Goals, reduce socio-political risks, and enhance government performance through transparency, public participation, and accountability for successes and failures. This paper tries to give an overview on the dynamic of e-government in Africa. Indeed, we use the concept of egovernment failure in this paper as the inability of a system to achieve predefined goals or unanticipated benefits. In fact, the EGDI helps us to underline the evolution and the challenges of African countries in digitalization. Africa, despite its immense potential and growing technological landscape, grapples with persistent challenges in the realm of egovernment development in Africa. The evolution of e-government in African countries, facing challenges like inadequate infrastructure, political commitment, and digital literacy. Despite these hurdles, tangible progress has been achieved. Furthermore crucial aspects and challenges still facing African countries such as interoperability, cybersecurity, Smart City services for urban development, and the growing role of Artificial Intelligence.
Keywords: African Research